National Cybersecurity in the Context of Society Digitalization: the Role of Police in Protecting Critical Infrastructure - V. M. Vasylenko (Bulletin of Kharkiv National University of Internal Affairs, 2025)
In the modern context of accelerated digital transformation, national cybersecurity has become a critical element of state policy aimed at protecting society, the economy, and national interests. The active integration of information and communication technologies into all spheres of public administration, economic processes, and everyday life not only generates new opportunities but also creates significant risks associated with cybercrime and the resilience of critical infrastructure. Against the backdrop of military aggression against Ukraine and large-scale cyberattacks targeting government agencies and strategic facilities, the effective operation of the national cybersecurity system is of particular relevance. This study focuses on analyzing the role of the police as a key actor within the cybersecurity system, responsible for law enforcement activities in cyberspace, prevention and investigation of cybercrime, and cooperation with other government bodies, incident response teams (CERT/CSIRT), private sector entities, and civil society organizations. The purpose of the research is to identify current approaches to shaping an effective model of police interaction in ensuring national cybersecurity and to explore legal, organizational, and practical aspects of police engagement in protecting critical infrastructure. The study reviews the current legal framework in Ukraine on cybersecurity, including the Law of Ukraine “On Basic Principles of Ensuring Cybersecurity of Ukraine”, the Law “On Critical Infrastructure”, as well as European and international documents such as the NIS2 Directive and the Budapest Convention on Cybercrime. The research methodology is based on systemic, comparative-legal, analytical, and formal-legal methods. The scientific novelty lies in the comprehensive examination of the legal regulation of police activities in cybersecurity and the identification of key directions for improving interagency cooperation amid growing cyber threats. The theoretical significance of the study lies in enhancing the academic understanding of the police’s role in ensuring cybersecurity and in developing legal mechanisms for their activities. The practical significance lies in formulating recommendations for improving legal regulations and enhancing collaboration between the police, CERT structures, private companies, and civil society. The research concludes that systemic approaches must be adopted to increase the effectiveness of police work in cybersecurity, aligned with European standards and international best practices, as a crucial factor in strengthening national resilience against cyber threats.